(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
The aim of the study isto study the features of central hemodynamics in patients with diffuse toxic goiter. Material and methods of research. 32 people were examined, including 22 women, 10 men, average age49.2±1.62years (for women -47±1.76years, for men -42±2.6years) Research methods – general clinical, biochemical (bilirubin, direct, indirect, ALT, AST, PTI, coagulogram, CRP), hormonal (TSH, free thyroxine, antibodies to thyroid peroxidase, to thyroglobulin and thyrocyte receptors, prolactin in the blood),anthropometric calculations (height (cm), weight (kg), BMI (kg/m2), waist circumference, waist circumference) and instrumental: ECG, echo-ECG, ultrasound of the thyroid gland, internal organs, chest X-ray Research results. When analyzing echocardiography data in patients with thyrotoxicosis syndromevisiblethat in the general group of patients, a reliable decrease in the indicators of end-diastolic volume and end-diastolic volume and a reliable decrease in the ratio of peaks E and A in relation to the control were observed. An analysis of echocardiography parameters in patients with thyrotoxicosis depending on the clinical form showed that in the overt form, the EDV and ESV values, peak E, and the E/A ratio are significantly reduced. In the subclinical form, the IVS and peak A values are significantly increased, and a significant decrease in ESV is observed. Conclusions.Echocardiographic signs of hemodynamic disturbances in thyrotoxicosis can be detected even before the manifestation of clinical symptoms of thyrotoxic heart disease.